Environmental Movement of KRESEK Kudus Community In Increasing Public Awareness of Environment - Qodarsasi, Umi (Institut Agama Islam Negeri (IAIN) Kudus, 2022)
Along with the increasing of population density, the problem of waste is threatens environmental sustainability. especially the type of waste that cannot be recycled. The amount of waste produced by residents in Kudus Regency is very large. Every day, the garbage that enters the Tanjungrejo Final Disposal Site (TPA) reaches 130 tons. TPA Tanjungrejo has an area of 5.6 hectares and is currently unable to accommodate the waste. The waste problems have encouraged the Kresek Kudus community to initiate an environmental conservation movement. This research aims to determine the effort of KRESEK to increase public awareness about environment. This research uses a qualitative approach and descriptive method. The primary data in this research were obtained by in-depth interviews towards the leader and volunteers of KRESEK Kudus, while the secondary data was conducted by literature study. The results of this research consist of (1) maintaining the continuity of the movement through the cadre of environmental agents, especially among young people; (2) building cooperation with stakeholders and village communities; and (3) using social media to campaign for environmental awareness.